(untitled) (Sains Humanika, 2008)
The purpose of this research is to measure the level of students’ geometrical thinking after using a newly developed module based on Form Two topic on Circles using an Interactive Geometry software (IGS). The research comprises of two phases which are the development phase and the implementation phase. In the development phase, a learning module using KDE Interactive Geometry (KIG) software was developed. The questions in the module were developed based on the levels as proposed in the Van Hiele Model which are visualization, analysis and informal deduction. In the implementation phase, the developed module was then used as a treatment on three Form Two students involving one–group of pre–test post–test research design. The students were chosen randomly and they were given a pre and post test before and after the learning sessions of circles using IGS. While using the module, the students’ conversations with the researcher were recorded. The transcript was then analysed to determine the types of critical and creative thinking utilised by the students. The critical and creative thinking indicators as suggested by the Curriculum Development Centre were referred. The students’ work completed in the module, together with their work saved in hard disk were analysed for the purpose of identifying the students’ geometrical thinking levels. The results showed that the students were able to utilise various types of critical and creative thinking while solving the questions in the module. In addition, the students were also able to achieve the third level of geometrical thinking as proposed in van Hiele Model. The post test results indicated that the students’ geometrical thinking showed clear improvement after using the module.